Papel da contratação sustentável pela administração pública brasileira: um estudo sobre os contratos de natureza contínua na Universidade Federal de Uberlândia - Alves, Cleyton Caixeta (2020)
This study addresses the topic of sustainable public procurement. The concern with sustainable development has become more evident over time, and with that we have sought to develop mechanisms and legal instruments with the intention of a more sustainable public administration, aiming at the balance between society and the environment. The fact that public institutions have a high purchasing power ends up generating major impacts on the economic, social and environmental environment, and the encouragement of more ecologically sustainable practices within the procurement process is the mechanism for government evolution. Within the public procurement process, it is important that administrative agencies assume this strategic role, seeking to manage public resources within the precepts established by law, seeking to reduce the impacts resulting from this evolution on the environment, with instruments aimed at sustainable development. In view of this, this work intends to analyze public contracts in the scope of the Brazilian federal public administration, more precisely from a federal public university located in the Triângulo Mineiro region and their role as promoters of sustainable practices in bidding organizations. The field research started from secondary data on the portal of the Federal University of Uberlândia and later identified which companies contributed to the sustainable public procurement policy. Then those responsible for these bidding organizations were interviewed. The results reveal that even with the efforts of the federal legislation, sustainable public procurement still represent a small portion of the total acquired by the federal government. And that the bidding companies encounter barriers to be able to put sustainability into practice in contracts, such as high prices, little information in the notices and. This research contributes theoretically to expand the knowledge about the theory of sustainability applied to the Brazilian public administration as well as to public servants who are interested in the results achieved by the measures taken, in order to replicate it in other Brazilian public agencies.